2002
DOI: 10.1002/art.10624
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies to lipoprotein lipase and dyslipidemia in systemic lupus erythematosus

Abstract: Objective. To demonstrate the binding of bovine lipoprotein lipase (LPL) by IgG from sera obtained from patients with systemic lupus erythematosus (SLE) and other rheumatic diseases, and the relationship of anti-LPL to triglyceride levels in SLE.Method. Binding of LPL by IgG from sera obtained from patients with SLE and other rheumatic diseases was measured by an enzyme-linked immunosorbent assay technique. Lipid profiles for fasting blood samples obtained from SLE patients and control subjects were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
83
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(94 citation statements)
references
References 20 publications
8
83
0
3
Order By: Relevance
“…This brings to light the question previously raised by Reichlin of distinct subpopulations of autoantibodies against LPL, perhaps there is a population that has an inhibitory activity on the enzyme and other population not functionally active. 4 Our study showed titer fluctuation of anti-LPL antibodies in those individuals with concomitant lupus clinical and laboratory activity. On the other hand, in those other patients who were in remission for years, anti-LPL antibodies were present, in high titers and with no significant variation.…”
Section: Discussionsupporting
confidence: 47%
See 3 more Smart Citations
“…This brings to light the question previously raised by Reichlin of distinct subpopulations of autoantibodies against LPL, perhaps there is a population that has an inhibitory activity on the enzyme and other population not functionally active. 4 Our study showed titer fluctuation of anti-LPL antibodies in those individuals with concomitant lupus clinical and laboratory activity. On the other hand, in those other patients who were in remission for years, anti-LPL antibodies were present, in high titers and with no significant variation.…”
Section: Discussionsupporting
confidence: 47%
“…Nesse sentido, os anticorpos antilipoproteína lipase (anti-LPL), recentemente descritos no LES 4 , foram correlacionados à hipertrigliceridemia, à proteína C-reativa de alta sensibilidade e à atividade de doença através do systemic lupus erythematosus disease activity index (SLEDAI). 5 A lipoproteína lipase (LPL) é uma enzima presente na superfície endotelial que tem como função a hidrólise de quilomícrons e triglicérides 6 e já foi demonstrada que a sua função reduzida está relacionada à hipertrigliceridemia.…”
Section: Introductionunclassified
See 2 more Smart Citations
“…Furthermore, lipoprotein lipase antibodies in SLE patients can contribute to the high TG levels. The alterations in the TG metabolism can cause changes primarily in HDL and also other lipids [14,15]. The reasons for low HDL levels are the apoprotein A-1 synthesis in the liver and alterations in the lecithin cholesterol acyl transferase activity.…”
Section: Discussionmentioning
confidence: 99%